2014
DOI: 10.1002/ijop.12064
|View full text |Cite
|
Sign up to set email alerts
|

Why employees with higher challenging appraisals style are more affectively engaged at work? The role of challenging stressors: A moderated mediation model

Abstract: Challenging stressors have been positively linked to various work outcomes. However, the role of individual differences in stress appraisal in shaping the function of challenging stressors and work outcomes has been rarely discussed. Drawing on the individual differences perspective, the authors propose that employees higher in challenge appraisal are more likely to have challenging stressors and are more responsive to such stressors to have a higher positive affect at work. Results obtained from 117 employees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…For example, Leinhos et al (2018) showed that the positive effect of time pressure on work engagement is only present, when considering additional task-specific resources such as time control. Further, Lin et al (2014) highlighted the meaning of challenge appraisal processes as necessary boundary condition, if challenge stressors unfold a positive potential. This is in line with Tuckey et al (2015), who highlighted the meaning of available resources to successfully cope and prevent the development of chronic stress when experiencing challenging conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Leinhos et al (2018) showed that the positive effect of time pressure on work engagement is only present, when considering additional task-specific resources such as time control. Further, Lin et al (2014) highlighted the meaning of challenge appraisal processes as necessary boundary condition, if challenge stressors unfold a positive potential. This is in line with Tuckey et al (2015), who highlighted the meaning of available resources to successfully cope and prevent the development of chronic stress when experiencing challenging conditions.…”
Section: Discussionmentioning
confidence: 99%
“…These extraordinary efforts of employees ultimately derive successful OP. Exciting work assignments with high challenge appraisal positively influence the job performance of employees (Lin et al, 2014). The research work of Williams et al (2007) established that the gratitude of employees on account of wage revision could encourage their work performance.…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%
“…However, this turn in affect trajectories in the mid to late 60s should not affect the working population as most people retire before the downward trend in affective wellbeing would set in. Indeed, several cross-sectional studies focusing on worker samples yielded higher levels of positive affect and/or lower levels of negative affect with age (Dahling & Perez, 2010;Lin, Wu, Chen, & Chen, 2014;Wegge, van Dick, Fisher, West, & Dawson, 2006;Yeung, Wong, & Lok, 2011), although other studies find age to be unrelated to affect (Bindl, Parker, Totterdell, & Hagger-Johnson, 2012;Lee & Allen, 2002;Tavares, 2016;Yeung & Fung, 2012).…”
Section: Age Differences In Levels and Stability Of Workplace Affectmentioning
confidence: 99%